2019
DOI: 10.3390/app9163236
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-Related Foot Function Analysis: Implications for Jumping and Running

Abstract: Barefoot and shod running has received increased attention in recent years, however, the influence of morphology-related foot function has not been explored. This study aimed to investigate morphology-related jumping and running biomechanical functions in habitually barefoot and shod males. A total of 90 barefoot males (Indians) and 130 shod males (Chinese), with significant forefoot and toe morphology differences, participated in a vertical jump and running test to enable the collection of kinematic and kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(89 reference statements)
1
1
0
Order By: Relevance
“…The ML models’ performance were compared based on their resulting RMSE, MAE, and R 2 against the OpenSim and CEINMS output (used here as ground truth). The computed OpenSim joint angles and moments waveforms found in this study were similar to the literature 49 , 50 . Muscle forces computation were validated by comparing them to the experimental EMG recordings.…”
Section: Discussionsupporting
confidence: 85%
“…The ML models’ performance were compared based on their resulting RMSE, MAE, and R 2 against the OpenSim and CEINMS output (used here as ground truth). The computed OpenSim joint angles and moments waveforms found in this study were similar to the literature 49 , 50 . Muscle forces computation were validated by comparing them to the experimental EMG recordings.…”
Section: Discussionsupporting
confidence: 85%
“…Ridge et al 10 found that larger peak flexion angles in knee and hip joint during UGT at FWS than NWS. Larger sagittal knee ROM may be a compensatory movement due to the increased gait speed 20 , resulting from greater knee impact during UGT. Subjects stabilized with larger range of hip, knee, and ankle joints motion, which may contribute to faster terminating times, but may also need greater joint extensor activity for stability 21 .…”
Section: Discussionmentioning
confidence: 99%